Analysis of Factors Influencing Pregnant Women in the Completeness of Antenatal Care Visits in The Work Area UPTD Puskesmas Drien Jalo - Maqfirah, Ulfa; Suroyo , Razia Begum; Wulan , Mayang; Anggraini , Indah; Sibero, Jitasari (Hasanuddin Medan, 2023)
Antenatal care, or ANC, is the term for care connected to pregnancy for both the mother and the fetus. At present, there are around 305 maternal deaths for every 100,000 live births; most of these deaths occur in hospitals. Among other causes, 77% of women pass away there as a result of referrals. This study examines how expectant mothers complete prenatal care visits in 2023 in the Meukek District of the South Aceh Regency's Drien Jalo Health Center's UPTD Working Area. This type of study uses a combination of methodologies. The population of this study consisted of 112 respondents, of whom 53 were randomly chosen based on qualitative information obtained from 9 informants, using the Slovin algorithm. The variable results are included in the multivariate test because the P value is ? 0.25. Multivariate analysis results show significant values ??and Exp(B) variables are, Knowledge (0.015) Exp(B) (3.572), Education (0.001) Exp(B) (0.007), Attitude (0.018) Exp(B) (1.398), Parity (0.009) Exp(B) (1.786), Income (0.000) Exp(B) (0.008), Distance (0.001) Exp(B) (1.904), Maternal Health (0.005) Exp(B) (1.556), Support Health Officer (0.001) Exp(B) (2.387). From the results of in-depth interviews, it was found that there was an influence on the completeness of ANC visits on the factors of knowledge, education, attitude, parity, income, distance, maternal health and support from health workers. The study's findings indicate that the completion of antenatal care visits is influenced by a number of factors, including maternal health, parity, money, distance, knowledge, education, attitude, and assistance from healthcare professionals. With an Exp(B) value of 3.572, the knowledge factor is the most important factor influencing ANC tests in expectant mothers.